Dynamics of Decision-Making to Stop Consuming Alcoholic Beverages in Former Alcoholism - Ratu, Yohanes; Mage, Mernon Yerlinda Carlista; Pello, Shela Christine; Junias, Marylin Susanti (Journal of Health and Behavioral Science, 2024)
Decision-making is a cognitive process carried out to find the most appropriate alternative to change a behaviour, and it also occurs in alcoholic individuals to consider the cause and effect experienced to stop being alcoholic. Alcoholism is a term used for individuals who use and consume alcohol over long periods. The purpose of this study is to be able to describe how the dynamics of decision-making to stop consuming alcoholic beverages in former alcoholism based on perceptions, attitudes and behaviours that arise during the process of stopping consuming alcohol. The type of research used is qualitative with a phenomenological approach. Participants in this study amounted to 5 people in Kupang City. The results obtained showed that the initial perception of participants to decide to stop consuming alcohol due to feeling the adverse effects on themselves and the surrounding environment, then the participants began to take a stand by looking for and doing activities that can be used to stop consuming alcohol and behaviours that can be seen namely social support, reinforcement and modelling.